1973
DOI: 10.1126/science.182.4118.1271
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and the Biosynthesis of Ascorbic Acid

Abstract: The ability to synthesize ascorbic acid is absent in the insects, invertebrates, and fishes. The biosynthetic capacity started in the kidney of amphibians, resided in the kidney of reptiles, became transferred to the liver of mammals, and finally disappeared from the guinea pig, the flying mammals, monkey, and man. A similar transition in the biosynthetic ability was observed in the branched evolution of the birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
1
2

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(227 citation statements)
references
References 30 publications
5
217
1
2
Order By: Relevance
“…Most vertebrates synthesize ascorbic acid endogenously, because of its important antioxidant functions, but anthropoid primates, fruit bats, guinea pigs, and many birds have lost this capacity (52). Among the primates, all prosimians except Tarsiers also synthesize ascorbic acid endogenously.…”
Section: Case 2 External Redundancymentioning
confidence: 99%
“…Most vertebrates synthesize ascorbic acid endogenously, because of its important antioxidant functions, but anthropoid primates, fruit bats, guinea pigs, and many birds have lost this capacity (52). Among the primates, all prosimians except Tarsiers also synthesize ascorbic acid endogenously.…”
Section: Case 2 External Redundancymentioning
confidence: 99%
“…This is supported by location on the same chromosome as SAP and CRP. Functionality of human Mptx may subsequently be lost in the human lineage, as has been described for vitamin C synthesis [6]. It was shown that in humans, other primates and guinea pigs, L-gulono-c-lactone oxidase, which catalyzes the terminal step in L-ascobic acid biosynthesis, is lacking [22].…”
Section: Discussionmentioning
confidence: 90%
“…We tested for the occurrence of the fluorescent band on gels with the microsomal preparations of 324 tissues of various animals. The microsomes of rabbit liver, chicken kidney and bullfrog kidney, which are known to contain L-gulono-y-lactone oxidase [8], all gave a fluorescent band. The migration distance of each band was the same within the experimental error.…”
Section: Resultsmentioning
confidence: 99%
“…The microsomal preparations of carp hepatopancreas and kidney gave no fluorescent band, either. Since all these microsomal preparations that did not give the fluorescent band are reported to have no enzymic activity [8], localization of L-gulono-ylactone oxidase on SDS-polyacrylamide gels by its intrinsic fluorescence seems to provide a means of detecting the enzyme with crude preparations.…”
Section: Resultsmentioning
confidence: 99%